2015
DOI: 10.1590/s1679-45082015ao3216
|View full text |Cite
|
Sign up to set email alerts
|

Check-up and cardiovascular risk progression: is there a room for innovation?

Abstract: Objective:To evaluate the impact of traditional check-up appointment on the progression of the cardiovascular risk throughout time.Methods:This retrospective cohort study included 11,126 medical records of asymptomatic executives who were evaluated between January, 2005 and October, 2008. Variables included participants’ demographics characteristics, smoking habit, history of cardiovascular diseases, diabetes, dyslipidemia, total cholesterol, HDL, triglycerides, glucose, c-reactive protein, waist circumference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In our study, it is possible that the wellness promoted by physical exercise affected the perception of risk. In another retrospective cohort study that included 3150 participants and evaluated the impact of traditional checkup appointments on the progression of CV risk over time, most CV risk factors worsened over time, meaning that the clinical evaluation, all medical education, and all pharmacologic and nonpharmacologic interventions had little effect on patient behavior . Extrapolating these findings to our study, it might be possible that the use of medications also had minimal effect on individuals' perception of risk.…”
Section: Discussionmentioning
confidence: 58%
“…In our study, it is possible that the wellness promoted by physical exercise affected the perception of risk. In another retrospective cohort study that included 3150 participants and evaluated the impact of traditional checkup appointments on the progression of CV risk over time, most CV risk factors worsened over time, meaning that the clinical evaluation, all medical education, and all pharmacologic and nonpharmacologic interventions had little effect on patient behavior . Extrapolating these findings to our study, it might be possible that the use of medications also had minimal effect on individuals' perception of risk.…”
Section: Discussionmentioning
confidence: 58%
“… 84 Specifically, the Brazil study showed poorer serum lipid levels and no significant mean BP changes. 84 Regular risk assessments that integrate patient education and self-management strategies are essential to reduce the potential adverse CVD outcomes among hypertensive patients. In the present study, the finding of significant relationships between participants’ underestimation and overestimation of subjective risk perceptions with HTN duration and frequency of physician visits was a counterintuitive finding, which may be encountered due to prevalent poor CVD risk perceptions.…”
Section: Discussionmentioning
confidence: 92%
“…A retrospective, large cohort study (n = 3150) of adults in Brazil followed for two years to examine the progression of CVD risk using the FRS showed those classified as moderate to high risk at year one follow-up showed a 31% increase in CVD risk at year two. 84 In addition, 66% of those who were classified as high CVD risk in the first assessment did not exhibit improved risk status at year two follow-up. 84 Specifically, the Brazil study showed poorer serum lipid levels and no significant mean BP changes.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation